THU0235 Identifying and quantifying prognostic factors in systemic sclerosis-related interstitial lung disease using a time-varying covariate survival model. (23rd January 2014) - Moore, O.A.; Goh, N.; Corte, T.; Rouse, H.; Hennessy, O.; Thakkar, V.; Byron, J.; Sahhar, J.; Roddy, J.; Youssef, P.; Nash, P.; Zochling, J.; et al.
Abstract : Background: Interstitial lung disease (ILD) is a leading cause of mortality in systemic sclerosis (SSc). We have shown that total extent of lung disease on high-resolution CT (HRCT) lung, reported using a simple grading system, [1] can determine prognosis in SSc-ILD. Objectives: We assessed factors that predicted deterioration in ILD using a time varying covariate model. Methods: SSc patients with a baseline HRCT around the time of diagnosis of ILD were identified through the Australian Scleroderma Cohort Study (ASCS). All HRCTs and pulmonary function tests (PFTs) performed during follow-up were retrieved. Demographic and disease-related data were prospectively collected in the ASCS database. HRCTs were reported by three blinded raters (two respiratory physicians, one radiologist) following a training session. Scans were graded according to the percentage of lung disease seen; >20% - extensive, <20% - limited, unclear - indeterminate. Indeterminate results were converted to limited or extensive using an FVC threshold of 70%. The composite outcome variable was deterioration (defined as need for home oxygen or lung transplantation) or death. Demographic and disease related data including HRCT grade was compared to outcome using a Weibull hazards regression model with time-varying covariates. Results: Among 172 patients followed for mean±SD of 3.47±2.93 years, there were 33 outcome events. In time-varying covariate models (based on 1309 serial PFTs and 353 serial HRCTs in the 172 patients), serial DLCO/VA (ml/min/mmHg/L) (adjusted hazards ration (aHR) =0.4, 95% CI: 0.3-0.7, p=0.001), FVC (dL) (aHR =0.9, 95% CI: 0.8-0.97, p=0.008) and extensive disease score (aHR =3.3, 95% CI: 1.1-9.9, p=0.03), were strongly predictive of outcome. Conclusions: In follow-up of patients with SSc-ILD findings of extensive disease according to this simple staging system or lower DLCO/VA or FVC are indicative of increased risk of poor disease outcome. Considering the cost and radiation risk of HRCT-lung we would suggest the use of PFTs in the follow-up of these patients. References: Goh NSL, Desai SR, Veeraraghavan S, et al. Interstitial Lung Disease in Systemic Sclerosis: A Simple Staging System. American Journal of Respiratory and Critical Care Medicine 2008;177:1248–1254. Disclosure of Interest: None Declared